1999
DOI: 10.1007/s004150050322
|View full text |Cite
|
Sign up to set email alerts
|

Blink reflex in trigeminal hypoesthesia caused by a pontine demyelinating lesion

Abstract: Sirs: The blink reflex (BR) test evaluates the integrity of the trigeminalfacial arc. Unilateral electrical stimulation of the supraorbital nerve evokes two separate contractile responses in the orbicularis oculi muscle. The early (R1) component is evoked only on the side of stimulation as a pontine reflex, whereas the late (R2) component is recorded bilaterally and is presumed to be relayed through polysinaptic pathways of the pons and the lateral medulla. We report a case of trigeminal hypoesthesia with abno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…In our opinion, there is evidence in favour of a relation between the two pathologies: the MRI of the demyelinating lesion showed that it was located exactly in the trigeminal nerve root inlet area, thus involving the trigeminovascular circuit. In addition the anomalies of the blink reflex are also consistent with the presence of a lesion in the pontine trigeminal nucleus [8].…”
Section: Commentssupporting
confidence: 68%
“…In our opinion, there is evidence in favour of a relation between the two pathologies: the MRI of the demyelinating lesion showed that it was located exactly in the trigeminal nerve root inlet area, thus involving the trigeminovascular circuit. In addition the anomalies of the blink reflex are also consistent with the presence of a lesion in the pontine trigeminal nucleus [8].…”
Section: Commentssupporting
confidence: 68%